Journalism and the Digital Age: An Analytical Study - Arpita Sneh (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2025)
The digital age has brought about unprecedented changes in the nature, structure, and functioning of journalism. Moving beyond traditional print and broadcast media, journalism is now emerging in new forms through the internet, social media, mobile technology, and artificial intelligence. The speed of information production, dissemination, and consumption has become much faster than before. This transformation has, on the one hand, promoted democratic participation, freedom of expression, and citizen journalism, while on the other hand, it has also created serious challenges such as fake news, information credibility, media ethics, and commercial pressures. This research paper analyzes the development, form, impact, opportunities, and challenges of journalism in the digital age and attempts to understand how digital technology is redefining the role of journalism. The study also clarifies that in the digital age, journalism is no longer merely a medium of information but has become an interactive, multidimensional, and people-centric process.